Identification of YAP1 as a novel downstream effector of the FGF2/STAT3 pathway in the pathogenesis of renal tubulointerstitial fibrosis. Issue 11 (16th May 2021) - Li, Xiaoying; Zhang, Fan; Qu, Lingling; Xie, Ying; Ruan, Yuanyuan; Guo, Ziwei; Mao, Yanwen; Zou, Qin; Shi, Mingjun; Xiao, Ying; Wang, Yuanyuan; Zhou, Yuxia; et al.
Abstract: Chronic kidney disease is a global health problem and eventually develops into an end‐stage renal disease (ESRD). It is now widely believed that renal tubulointerstitial fibrosis (TIF) plays an important role in the progression of ESRD. Renal tubular epithelial‐mesenchymal transition (EMT) is an important cause of TIF. Studies have shown that FGF2 is highly expressed in fibrotic renal tissue, although the mechanism remains unclear. We found that FGF2 can activate STAT3 and induce EMT in renal tubular epithelial cells. STAT3, an important transcription factor, was predicted by the JASPAR biological database to bind to the promoter region of YAP1. In this study, STAT3 was shown to promote the expression of the downstream target gene YAP1 through transcription, promote EMT of renal tubular epithelial cells, and mediate the occurrence of renal TIF. This study provides a theoretical basis for the involvement of the FGF2/STAT3/YAP1 signaling pathway in the process of renal interstitial fibrosis and provides a potential target for the treatment of renal fibrosis. Abstract : The FGF2/STAT3/YAP1 signaling pathway in the pathogenesis of tubulointerstitial fibrosis. In this pathway, FGF2 stimulates the activation of STAT3 and induces YAP1 transcription in renal tubular epithelial cells. Specifically, STAT3 directly binds to the promoter of YAP1 and regulates the YAP1 mRNA at the transcriptional level. The signaling is contributed to promote the occurrence and development of renal interstitial fibrosis.